2011
DOI: 10.5539/ass.v7n8p49
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support and Self-Esteem towards Gender Roles: Contributing Factors in Adolescents

Abstract: The study aims to examine the relationship between self-esteem and perceived social support among the Malaysian adolescents. Gender differences of perceived social support and self-esteem among the respondents were also investigated. To achieve the objectives of the study, a survey was conducted with a relatively large (n=460) random samples of adolescents, aged 16-20, drawn from schools, colleges and universities in Malaysia. The Self-esteem Rating Scale (SERS) and the Multidimensional Scale of Perceived Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
4
15
1
Order By: Relevance
“…Correlation analysis showed that PSS, SE and PWB had significant relationship with each other. These results are consistent with previous studies that reported the relationship between PSS and SE [14,16,21,32,[40][41][42][43], PSS and different aspects of wellbeing [12,[14][15][16][43][44][45], SE and wellbeing as well as happiness [14,16,20,43,46]. Moreover, the most important finding of this study is that SE fully mediated the relationship between PSS and PWB suggesting adolescents with high levels of social support are likely to have higher SE which in turn enhances their PWB.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Correlation analysis showed that PSS, SE and PWB had significant relationship with each other. These results are consistent with previous studies that reported the relationship between PSS and SE [14,16,21,32,[40][41][42][43], PSS and different aspects of wellbeing [12,[14][15][16][43][44][45], SE and wellbeing as well as happiness [14,16,20,43,46]. Moreover, the most important finding of this study is that SE fully mediated the relationship between PSS and PWB suggesting adolescents with high levels of social support are likely to have higher SE which in turn enhances their PWB.…”
Section: Discussionsupporting
confidence: 93%
“…Female adolescents as compared to male adolescents are more oriented toward peers for social support and are also more satisfied with the support gained from their peers [31]. However, no gender differences in SE and PSS were reported in the study conducted among the Malaysian adolescents [32]. Based on the literature review it can be concluded that much research has been done in relation to gender differences in PSS, SE and PWB but results are inconclusive.…”
Section: Introductionmentioning
confidence: 88%
“…Child physical abuse has been negatively associated with perceptions of support from family and friends and is generally related to lower levels of perceived social support in adulthood ( Runtz and Schallow, 1997 ; Crouch et al, 2001 ; Vranceanu et al, 2007 ; Sperry and Widom, 2013 ). Students with lower perceived levels of social support from their classmates are more likely to have lower levels of self-esteem and higher levels of depression ( Wolchik et al, 1989 ; Tam et al, 2011 ). Numerous empirical studies have shown that higher perceived social support is positively correlated with high self-esteem ( Hoffman et al, 1988 ; Tam et al, 2011 ; Kong et al, 2012b ; Kong and You, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Students with lower perceived levels of social support from their classmates are more likely to have lower levels of self-esteem and higher levels of depression ( Wolchik et al, 1989 ; Tam et al, 2011 ). Numerous empirical studies have shown that higher perceived social support is positively correlated with high self-esteem ( Hoffman et al, 1988 ; Tam et al, 2011 ; Kong et al, 2012b ; Kong and You, 2013 ). The mediating effect of self-esteem is in line with previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation